ANALISIS RANGKA ATAP BAJA PADA GEDUNG I RSUD GAMBIRAN KEDIRI - Moch. Arsyad Adrianto; M. Rizki Adi Taruna; Nia Dwi Puspitasari (LPPM Universitas Abdurrab, 2026)
This research aims to analyze the dead load and live load acting on the steel roof truss structure of Building I, Gambiran Regional General Hospital (RSUD) Kediri. The WF steel roof structure serves a crucial function as the primary protection for the building against environmental factors. The analysis was conducted through three-dimensional (3D) structural modeling using the SAP2000 version 26 software. The methodology involved collecting technical data (including WF 250.125.6.9 steel profiles, Galvalum 5 kg/m2, and a roof slope of 15°) and conducting load analysis based on SNI 1727:2020 and SNI 1726:2019. The loads considered include dead loads (steel and roof covering), roof live loads, rain loads, and wind loads.